CONTRIBUTION OF CANCER STEM CELLS TO THE METASTATIC MECHANISM IN POSITIVE LMP I WHO TYPE III NASOPHARYNGEAL CANCER PATIENT BEFORE AND AFTER NEOADJUVANT CHEMOTHERAPY - Pudji Rahaju; Anis Eko Kristiawan; Endang Retnoningsih (TALENTA PUBLISHER, 2019)
Introduction Nasopharyngeal cancer is the most common malignant tumour of the head and neck that caused high mortality. Most of patients came for treatment in late stage with enlargement of the neck lymphnode. Cancer stem cells are characteristic of stemness such as self-renewal and survival that caused tumour metastasis and recurrence. CD44, SOX2 and CCR7 are marker for NPC stem cells. Method Nine new patients NPC, WHO type III, positive LMP1 were examined for volume of the neck lymphnode, CD44, SOX2 and CCR7 expression before and after treatment chemotherapy cisplatin based. Staging determined by AJCC/UICC 2010. Result The results of this study showed that all subjects have increased SOX2 and CCR7 expression after treatment with statistically negative correlation. CD44 did not altered before and after treatment and cannot be evaluate. Correlation between alteration of the increase SOX2 and CCR7 expression and reduction of the volume have shown statistically positive correlation. Conclusion Neoadjuvant Chemotherapy Cisplatin based eliminated progenitor cells but did not for cancer stem cells in NPC. This result indicates that NPC with higher cancer stem cells must be more attention forward potential resistance and recurrence of the tumour. Although the have received all Stanford treatment